Effect of Body Weight Change on Blood Pressure in a Japanese General Population with a Body Mass Index ≥ 22 kg/m2: A Community-Based Cohort Study - Kaneko, Hidehiro; Daimon, Masao; Morita, Hiroyuki; Nakanishi, Koki; Itoh, Hidetaka; Kiriyama, Hiroyuki; Mizuno, Yoshiko; Yamamichi, Nobutake; Komuro, Issei (International Heart Journal, 2019)
The association between changes in body weight and blood pressure (BP) in overweight people in the general population still remains unclear. We sought to clarify the effect of body weight change on BP using a community-based cohort. We studied 1,170 overweight subjects with a body mass index (BMI) ≥ 22 kg/m2 who underwent health check-ups. Among the study subjects, 175 (15%) were categorized in the weight loss group (weight loss ≥ 5%), 869 (74%) in the weight stable group, and 126 (11%) in the weight gain group (weight gain ≥ 5%). There were no significant differences in baseline BP between the 3 groups. In the weight loss group, systolic and diastolic BP, and the rates of stage 2 (systolic BP ≥ 140 mmHg or diastolic BP ≥ 90 mmHg) and stage 1 hypertension (130 mmHg≤ systolic BP < 140 mmHg or 80 mmHg≤ diastolic BP < 90 mmHg) decreased. In contrast, in the weight gain group, systolic and diastolic BP and the rate of stage 2 hypertension increased. Subgroup analysis showed that the correlation between change in body weight and BP was seen in each subgroup according to age, sex, and BMI. The results of the present study suggest the significance of body weight control for BP control in subjects with BMI ≥ 22 kg/m2.